Leadership and Work Discipline as Determinants of Civil Servant Performance in Local Government Institutions - Efvy Zamidra Zam (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
This study aims to analyze the influence of leadership and work discipline on the performance of Civil Servants in Local Government. The research employed a quantitative approach using a survey method. The population consisted of twenty-four employees from a regional government organization, and the sampling technique used was saturated sampling, in which all population members were selected as respondents. Data were collected through questionnaires measured using a Likert scale. Data analysis was conducted using validity tests, reliability tests, multiple linear regression, t-tests, F-tests, and coefficient of determination analysis with the assistance of SPSS software. The results indicated that all research instruments were valid and reliable. Partially, leadership and work discipline had a positive and significant effect on employee performance. Simultaneously, leadership and work discipline also had a significant influence on the performance of Civil Servants. The coefficient of determination showed that leadership and work discipline explained most of the variance in employee performance. Furthermore, leadership was identified as the most dominant variable influencing employee performance. The findings indicate that improving leadership quality and strengthening work discipline can enhance the performance of civil servants in supporting effective public service delivery within local government institutions.